Tacit Knowledge Transfer and Sharing: Characteristics and Benefits of Tacit & Explicit Knowledge - Josephine Oranga (PT. Radja Intercontinental Publishing, 2023)
Knowledge is generally divided into two: Explicit (articulate) and Tacit. This article thus, explores the concept of tacit knowledge and the role that it plays in learning institutions and business organizations. Evidently, tacit knowledge is linked to knowledge management and as such, the world should utilize it for resilience-building and sustainable development. Notably, due to its complex nature, acquiring and extracting tacit knowledge is not easy as it is an unspoken, unwritten and hidden in people and ultimately leads to the well-being and success of individuals in society. Accordingly, tacit knowledge is very personalised, contextual and hard to communicate or transfer from one person to another by the process of verbal expression or writing and is generally made up of values, perceptions and beliefs. It is obtainable and transferrable through direct interaction amongst individuals and their environments. This paper, thus, explores tacit knowledge and assesses its role and significance in the advancement, enhancement and sustenance of learning and performances in business organisations and learning institutions. Accordingly, approximately 90% of the total knowledge in an organization is held in tacit form, ultimately, impacting the overall output and effectiveness of institutions and organizations.